Developing a Bilingual Website for Lestari Widodo Wiryotama Arts Studio - Dian Kartika Intan; Maya Rizki Fauzia (JLT Jurnal Linguistik Terapan, 2026)
Indonesian traditional dance is one of the art forms born from the diversity of Indonesian culture. In its preservation, dance art encounters various obstacles including technological advancement. A website for instance, allows younger generation to obtain information and entertainment quickly. However, there is a limited number of websites of which purpose is to preserve culture or traditional art. Therefore, the Lestari Widodo Wiryotama (LWW) website was developed to fill these gaps. The development of this website aims to be a medium of promotion and information for LWW Arts Studio, as well as an effort to take part in cultural preservation. This research uses the Design & Development Research (DDR) method with ADDIE model by Dick and Carey (1996), which includes analysis, design, development, implementation, and evaluation. This research concludes that the LWW Arts Studio website is adequate for promotional and informational purposes. It is expected to be a reference for other studies and to help LWW Arts Studio and future researchers develop.